PERAN GURU PPKn DALAM MENUMBUHKAN KESADARAN MORAL ANTI KORUPSI PADA SISWA DI SMP IT ADA KRINCING - Ramdhani, Muhammad; Hadi, Agustinus Sutriyanto; Muryati, Sri (Journal of Democratia; Vol 2 No 1 (2024): Jurnal Democratia : Pendidikan Pancasila dan Kewarganegaraan, Moral, Karakter, dan HukumDO - 10.31331/jade.v2i1.3063, 2024)
Corruption education is a conscious effort to provide understanding and prevention of acts of corruption committed from formal education in schools, informal education in the family environment, and non-formal education in the community. Most people may still think that corruption is only limited to the act of someone taking money that is not rightfully theirs. In fact, corruption can actually arise from various causes and even the place where corruption occurs is not only limited to the political arena. Education is recognized as the easiest and most effective strategy for changing, at least directing one's way of thinking and mindset in acting. Schools occupy a strategic position in implementing anti-corruption education, especially in cultivating anti-corruption behavior among students. Therefore the researchers conducted this research with the aim of finding out how the role of PPKN teachers is in raising anti-corruption moral awareness in students at SMP IT ADA Krincing. Using qualitative research methods, data collection techniques in this study were observation, interviews and documentation. The results of the analysis show that PPKn teachers at IT ADA Krincing Middle School have a role in growing anti-corruption moral awareness in students, teachers integrate noble values such as the values of justice, honesty, discipline, courage, responsibility, caring, simplicity, independence, and finally hard work.